1038 Sleep Disruption Experienced by Surgically Treated Brain Aneurysm Patients. (27th April 2018) - Virkkala, J; Martinez-Majander, N; Pakarinen, S; Niemelä, M; Putaala, J; Müller, K; Korja, M
Abstract: Introduction: Stress-related sleep disturbances are common. Major surgeries, such as cranial neurosurgery, induce a stress response that may alter the course of postoperative recovery. We objectively measured for the first time (to our knowledge) sleep disturbances in patients who were operated on for unruptured intracranial aneurysms. Methods: We measured the quality of sleep in 10 patients undergoing elective surgical treatment for unruptured intracranial aneurysms (age 26–62 years, 7 women). Ambulatory polysomnography was performed at home once preoperatively (1–22 days before surgery) and twice postoperatively (15–30 days after surgery and 5–32 days after first postoperative measurement). All patients were initially employed and working full-time. Exclusion criteria included a previous history of stroke, mental disturbances, or intracranial procedures. Patient-specific sleep variables (W, R, N1, N2, N3, SE, SL, PSL, WASO) were compared between pre- and postoperative measurements using Wilcoxon Signed-Rank Test. Results: None of the patients had neurological deficits following surgery. Second postoperative measurement was not available for two patients. Restorative non-rapid eye movement N3 sleep increased from the preoperative to the first postoperative measurement (17, 5, 123, 36, -1, 23, 8, 8, 6, 20 min; p=0.004). Also sleep latency (SL) time (p=0.04), persistent sleep latency (PSL) time (p=0.03), and total amount of wakefulness (W) in minutes (p=0.02) increased between the preoperative and the first postoperative measurements, whereas sleep efficiency (SE) decreased (p=0.03) at the same time. Between the first and second postoperative sleep measurements, there was an increase (48, 23, 51, -9, 11, NA, 0, 15, NA, 28 min; p = 0.03) of rapid eye movement R sleep. Conclusion: In this pilot study, postoperative sleep disturbances were evident after cranial neurosurgery. Increases in restorative sleep patterns after surgery may indicate normal recovery processes. N3 sleep changes may relate to preoperative psychological stress, which may disturb sleep already prior to surgery. REM sleep increase between first and second postoperative measurements may perhaps be used to assess timely recovery after cranial neurosurgery. Support (If Any): Finnish Funding Agency for Technology and Innovation.